2017
DOI: 10.4103/0971-3026.202951
|View full text |Cite
|
Sign up to set email alerts
|

Inguinoscrotal hernia in infants: Three case reports in ultrasound diagnosis

Abstract: An inguinal hernia occurs when an intestinal loop or part of the omentum or genital organs passes into the scrotal cavity or labia through an incompletely obliterated processus vaginalis. Inguinal hernias are most common in preterm neonates, especially at 32-weeks gestation. Content of hernia is mostly bowel and ovary/testicles. Presence of uterus in herniated sac is rare, and only few cases are reported in literature. Hernia is more frequently located on the right side because the right processus vaginalis cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In both sexes, right‐sided hernia are more common, possibly due to the typically later closure of the right processus vaginalis . Premature infants have an increased risk with up to 30% born with an inguinal hernia . Whilst 90% of indirect inguinal hernias in adults are due to a persistent processus vaginalis, in the paediatric population this is almost always the cause …”
Section: Anomalies Directly Related To Persistence Of the Processus Vmentioning
confidence: 99%
See 1 more Smart Citation
“…In both sexes, right‐sided hernia are more common, possibly due to the typically later closure of the right processus vaginalis . Premature infants have an increased risk with up to 30% born with an inguinal hernia . Whilst 90% of indirect inguinal hernias in adults are due to a persistent processus vaginalis, in the paediatric population this is almost always the cause …”
Section: Anomalies Directly Related To Persistence Of the Processus Vmentioning
confidence: 99%
“…4,5 Premature infants have an increased risk with up to 30% born with an inguinal hernia. 34 Whilst 90% of indirect inguinal hernias in adults are due to a persistent processus vaginalis, in the paediatric population this is almost always the cause. 2,5,35,36 Failure of closure of the processus vaginalis at the deep inguinal ring leaves an opening between the peritoneum and the inguinal canal, greatly increasing the likelihood of an indirect inguinal hernia in both paediatric and adult populations.…”
Section: Congenital Inguinal Herniamentioning
confidence: 99%
“…The diagnosis of obstructed hernia is always clinical. Ultrasound examination may be required if physical findings are inconclusive or in cases of acute scrotum [18]. Ultrasound can also be used in assessing peristalsis, wall thickness and vascularity of the bowel in the hernia sac [19].…”
Section: Discussionmentioning
confidence: 99%
“…Narrowing of the inner ring using primary sutures that is another procedure we recommend for giant hernias, forms a supporting tissue at the base of the inguinal canal. It prevents subcutaneous palpation of the hernia sac stump and evaluation of swelling in the inguinal region as recurrence by mistake during the effort movements especially in children with less weight [10]. Yokomori et al have narrowed the internal inguinal canal by a modified Marcy repair and reported in their series that this method was effective to prevent recurrence [11].…”
Section: Discussionmentioning
confidence: 99%